Circuit board interlayer adhesive and laminate
Patent Information
- Application Number
- JP2021000426
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-04
- Filing Date
- 2021-01-05
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-01-05
AI Technical Summary
【0012】 本発明の回路基板層間接着剤は、ポリオレフィン系樹脂を含有するため、比較的低誘電率であり、密着性および凹凸追従性に優れる。
Smart Images

Figure 0007645638000002 
Figure 0007645638000003 
Figure 0007645638000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a circuit board interlayer adhesive and a laminate. [Background technology]
[0002] 2. Description of the Related Art Wired circuit boards have been provided in various electronic devices and are manufactured, for example, by the following method.
[0003] That is, first, a first-layer circuit is formed on the copper foil of the carrier-attached copper foil. Next, the first-layer circuit is buried in a resin layer. Next, a second-layer circuit is formed on the resin layer. After that, the carrier is peeled off to expose the first-layer circuit. Also, epoxy resin and polyimide resin have been proposed as such a resin layer (see, for example, Patent Document 1).
[0004] In recent years, printed circuit boards are required to be compatible with high-frequency signals. Therefore, it has been proposed to use, as the resin layer, a fluororesin having a lower dielectric constant than epoxy resin and polyimide resin (for example, see Patent Document 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2014-225650 A [Patent Document 2] JP 2019-065061 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, when the resin layer of the wiring circuit board contains a fluororesin, there is a problem in that the adhesion between the resin layer and the conductor layer is low. Also, when the resin layer of the wiring circuit board contains a fluororesin, there is a problem in that the resin layer has low conformability to the conductor layer.
[0007] The present invention relates to a circuit board interlayer adhesive that has a relatively low dielectric constant and excellent adhesion and conformability to irregularities, and to a laminate obtained by using the circuit board interlayer adhesive. [Means for solving the problem]
[0008] The present invention [1] includes a circuit board interlayer adhesive containing a polyolefin resin.
[0009] The present invention [2] further includes the circuit board interlayer adhesive described in [1] above, which contains a fluorine-based resin and / or a polyphenylene ether resin.
[0010] The present invention [3] includes a laminate comprising a first conductor layer, a second conductor layer disposed opposite the first conductor layer, and an adhesive layer disposed between the first conductor layer and the second conductor layer and adhering the first conductor layer and the second conductor layer, the adhesive layer being made of the circuit board interlayer adhesive described in [1] or [2] above.
[0011] The present invention [4] includes a laminate comprising an insulating layer, a conductor layer disposed opposite the insulating layer, and an adhesive layer disposed between the insulating layer and the conductor layer and adhering the insulating layer and the conductor layer, the adhesive layer being made of the circuit board interlayer adhesive described in [1] or [2] above. Effect of the Invention
[0012] The circuit board interlayer adhesive of the present invention contains a polyolefin resin, and therefore has a relatively low dielectric constant and is excellent in adhesion and conformability to irregularities.
[0013] The laminate of the present invention has an adhesive layer made of the above-mentioned circuit board interlayer adhesive, and therefore the adhesive layer in the laminate has a relatively low dielectric constant and is excellent in adhesion and conformability to irregularities. [Brief description of the drawings]
[0014] [Figure 1]FIG. 1 is a process diagram for producing a circuit board as a first embodiment of a laminate, where FIG. 1A shows a process for preparing a copper foil with a carrier, FIG. 1B shows a process for forming a first resist layer, and FIG. 1C shows a process for forming a first conductor layer. [Diagram 2] FIG. 2 is a process diagram for manufacturing a multilayer circuit board following FIG. 1, in which FIG. 2D shows the step of removing the first resist layer, FIG. 2E shows the step of removing the copper foil exposed from the first conductor layer, FIG. 2F shows the step of laminating an adhesive layer, and FIG. 2G shows the step of laminating a copper foil with a carrier onto the adhesive layer. [Diagram 3] Figure 3 is a process diagram for manufacturing a multilayer circuit board following Figure 2, where Figure 3H shows the process of peeling off the carrier layer, Figure 3I shows the process of forming a via hole, Figure 3J shows the process of forming a via fill, and Figure 3K shows the process of forming a second resist layer. [Figure 4] Figure 4 is a process diagram for manufacturing a multilayer circuit board, following Figure 3, in which Figure 4L shows a process of forming a second conductor layer, Figure 4M shows a process of removing the second resist layer, Figure 4N shows a process of removing the copper foil exposed from the second conductor layer, and Figure 4O shows a process of peeling off the carrier layer 3. [Diagram 5] FIG. 5 is a schematic diagram showing a copper-clad laminate as a second embodiment of the laminate. [Figure 6] FIG. 6 is a schematic diagram showing a circuit board as a third embodiment of the laminate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] A circuit board interlayer adhesive is an adhesive used in the manufacture of a laminate (described below). The laminate (described below) refers to a circuit board or a circuit board material that can be processed into a circuit board.
[0016] The circuit board interlayer adhesive contains a polyolefin resin.
[0017] The polyolefin resin is an olefin homopolymer or an olefin copolymer. The olefin copolymer is a copolymer of an olefin and a copolymerizable monomer copolymerizable with the olefin. More specifically, the polyolefin resin includes unmodified polyolefin resins and modified polyolefin resins.
[0018] Examples of unmodified polyolefin resins include polyethylene, polypropylene, polyisobutylene, poly-1-butene, poly-4-methylpentene, polyvinylcyclohexane, polystyrene, poly-p-methylstyrene, poly-α-methylstyrene, ethylene-propylene copolymer, propylene-butene copolymer, styrene-ethylene-propylene-styrene copolymer, styrene-ethylene-butylene-styrene copolymer, ethylene-butene copolymer, ethylene-4-methyl-1-pentene copolymer, propylene-4-methyl-1-pentene copolymer, butylene-4-methyl-1-pentene copolymer, ethylene-hexene copolymer, and ethylene-vinyl acetate copolymer. Examples of copolymers include random copolymers and block copolymers (same below). These can be used alone or in combination of two or more types.
[0019] The modified polyolefin resin is a modified product of an unmodified polyolefin resin.
[0020] Examples of modified polyolefin resins include halogenated polyolefin resins, acid-modified polyolefin resins, and halogenated acid-modified polyolefin resins.
[0021] The halogenated polyolefin resin can be obtained by modifying an unmodified polyolefin resin with a halogen by a known method. Examples of halogen include fluorine, chlorine, bromine, and iodine. These can be used alone or in combination of two or more kinds. The halogen is preferably chlorine.
[0022] That is, examples of halogenated polyolefin resins include fluorinated polyolefin resins, chlorinated polyolefin resins, brominated polyolefin resins, and iodized polyolefin resins. These can be used alone or in combination of two or more. Examples of halogenated polyolefin resins include chlorinated polyolefin resins.
[0023] Examples of chlorinated polyolefin resins include chlorinated polyethylene, chlorinated polypropylene, chlorinated polyisobutylene, chlorinated poly-1-butene, chlorinated poly-4-methylpentene, chlorinated polyvinylcyclohexane, chlorinated ethylene-propylene copolymer, chlorinated propylene-butene copolymer, chlorinated styrene-ethylene-propylene-styrene copolymer, chlorinated styrene-ethylene-butylene-styrene copolymer, chlorinated ethylene-butene copolymer, chlorinated ethylene-4-methyl-1-pentene copolymer, chlorinated propylene-4-methyl-1-pentene copolymer, chlorinated butylene-4-methyl-1-pentene copolymer, chlorinated ethylene-hexene copolymer, and chlorinated ethylene-vinyl acetate copolymer. These can be used alone or in combination of two or more.
[0024] In the halogenated polyolefin resin, the halogenation ratio is not particularly limited and is appropriately set depending on the purpose and application.
[0025] The acid-modified polyolefin resin is obtained by modifying an unmodified polyolefin resin with an acid by a known method. Examples of the acid include unsaturated acids. Examples of the unsaturated acid include maleic acid, fumaric acid, itaconic acid, and (meth)acrylic acid. Examples of the unsaturated acid include anhydrides of these acids. These acids can be used alone or in combination of two or more. A preferred example of the unsaturated acid is maleic acid.
[0026] That is, examples of the acid-modified polyolefin resin include maleic acid-modified polyolefin resin, fumaric acid-modified polyolefin resin, itaconic acid-modified polyolefin resin, and (meth)acrylic acid-modified polyolefin resin. These can be used alone or in combination of two or more. As the acid-modified polyolefin resin, a preferred example is maleic acid-modified polyolefin resin.
[0027] Examples of maleic acid-modified polyolefin resins include maleic acid-modified polyethylene, maleic acid-modified polypropylene, maleic acid-modified polyisobutylene, maleic acid-modified poly 1-butene, maleic acid-modified poly 4-methylpentene, maleic acid-modified polyvinylcyclohexane, maleic acid-modified ethylene-propylene copolymer, maleic acid-modified propylene-butene copolymer, maleic acid-modified styrene-ethylene-propylene-styrene copolymer, maleic acid-modified styrene-ethylene-butylene-styrene copolymer, maleic acid-modified ethylene-butene copolymer, maleic acid-modified ethylene-4-methyl-1-pentene copolymer, maleic acid-modified propylene-4-methyl-1-pentene copolymer, maleic acid-modified butylene-4-methyl-1-pentene copolymer, maleic acid-modified ethylene-hexene copolymer, and maleic acid-modified ethylene-vinyl acetate copolymer. These can be used alone or in combination of two or more.
[0028] In the acid-modified polyolefin resin, the modification ratio is not particularly limited and is appropriately set depending on the purpose and application.
[0029] For example, the amount of the acid is, for example, 0.1 part by mass or more, preferably 0.5 part by mass or more, and for example, 20 parts by mass or less, preferably 10 parts by mass or less, relative to 100 parts by mass of the total amount of the acid-modified polyolefin resin.
[0030] The acid value of the acid-modified polyolefin resin is, for example, 0.1 mgKOH / g or more, preferably 0.5 mgKOH / g or more, and for example, 100 mgKOH / g or less, preferably 60 mgKOH / g or less.
[0031] The acid value is measured in accordance with JIS K 2501 (2003).
[0032] The halogenated acid-modified polyolefin resin can be obtained, for example, by halogenating an acid-modified polyolefin resin by a known method. The halogenated acid-modified polyolefin resin can be obtained, for example, by modifying a halogenated polyolefin resin with an acid by a known method.
[0033] These polyolefin resins can be used alone or in combination of two or more kinds.
[0034] As the polyolefin resin, preferably, a modified polyolefin resin is used, more preferably, an acid-modified polyolefin resin is used, further preferably, a maleic acid-modified polyolefin resin is used, and particularly preferably, a maleic acid-modified propylene-butene copolymer is used.
[0035] The weight average molecular weight of the polyolefin resin is, for example, 10,000 or more, preferably 50,000 or more, and for example, 500,000 or less, preferably 300,000 or less.
[0036] The weight average molecular weight of the polyolefin resin is measured by gel permeation chromatography in terms of a standard polystyrene molecular weight.
[0037] The melting point of the polyolefin resin is, for example, 30° C. or more, preferably 50° C. or more, and usually 150° C. or less.
[0038] The melting point is measured in accordance with JIS K 7122 (2012).
[0039] The polyolefin resin has a heat of fusion of, for example, 0 J / g or more, or preferably 5 J / g or more, and for example, 100 J / g or less, or preferably 60 J / g or less.
[0040] The heat of fusion is measured in accordance with JIS K 7122 (2012).
[0041] The circuit board interlayer adhesive may contain a polyolefin-based resin and may not contain other resins, that is, the circuit board interlayer adhesive may contain, for example, only a polyolefin-based resin.
[0042] The circuit board interlayer adhesive contains a polyolefin resin and may further contain other resins.
[0043] The other resins are resin components other than polyolefin resins, and examples of the other resins include fluorine-based resins, polyphenylene ether-based resins, and (meth)acrylic resins.
[0044] Examples of fluorine-based resins include polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinylidene fluoride, tetrafluoroethylene-ethylene copolymer, chlorotrifluoroethylene-ethylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-hexafluoropropylene-perfluoroethylene copolymer, and tetrafluoroethylene-hexafluoropropylene-perfluoroethylene-chlorotrifluoroethylene copolymer.
[0045] Examples of the fluorine-based resin include commercially available products, such as Fluon+ series (registered trademark, manufactured by AGC), Lumiflon series (registered trademark, manufactured by AGC), PTFE dispersion NS series (manufactured by Nagoya Gosei), and PTFE dispersion (manufactured by uni).
[0046] These fluorine-based resins can be used alone or in combination of two or more kinds.
[0047] Examples of polyphenylene ether resins include known polyphenylene ether resins, and modified polyphenylene ether resins obtained by alloying polyphenylene ether resins with other resins (such as polystyrene).
[0048] The polyphenylene ether resin may also be commercially available, such as Zylon S201A, Zylon S202A (both manufactured by Asahi Kasei), Noryl SA9000, Noryl SA90 (both manufactured by SABIC), Bestran 1900NC (manufactured by Daicel-Evonik), Iupiace LN23, and NX700 (both manufactured by Mitsubishi Engineering Plastics).
[0049] These polyphenylene ether resins can be used alone or in combination of two or more kinds.
[0050] Examples of the (meth)acrylic resin include a (meth)acrylic homopolymer and a (meth)acrylic copolymer. Here, (meth)acrylic refers to acrylic and / or methacrylic.
[0051] Examples of (meth)acrylic homopolymers include homopolymers of (meth)acrylic acid esters. Examples of (meth)acrylic acid esters include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, and phenyl (meth)acrylate. These can be used alone or in combination of two or more.
[0052] Examples of the (meth)acrylic copolymer include a copolymer of the above (meth)acrylic acid ester and a copolymerizable monomer. The copolymerizable monomer is a monomer that can be copolymerized with the (meth)acrylic acid ester. The copolymerizable monomer is not particularly limited, and includes known copolymerizable monomers. More specifically, examples of the copolymerizable monomer include a carboxy group-containing copolymerizable monomer, a hydroxy group-containing copolymerizable monomer, an amino group-containing copolymerizable monomer, a cyano group-containing copolymerizable monomer, a styrene-based monomer, and a vinyl ester-based monomer. These can be used alone or in combination of two or more kinds. The copolymerizable monomer is preferably a carboxy group-containing copolymerizable monomer.
[0053] Examples of the carboxyl group-containing copolymerizable monomer include maleic acid, fumaric acid, itaconic acid, and (meth)acrylic acid. Examples of the carboxyl group-containing copolymerizable monomer also include their anhydrides. These can be used alone or in combination of two or more kinds.
[0054] These (meth)acrylic resins can be used alone or in combination of two or more kinds. As the (meth)acrylic resin, preferably, a (meth)acrylic copolymer is used, and more preferably, a copolymer of a (meth)acrylic acid ester and a carboxyl group-containing copolymerizable monomer is used.
[0055] These other resins can be used alone or in combination of two or more kinds. As the other resins, preferred are fluorine-based resins and polyphenylene ether-based resins.
[0056] In other words, the circuit board interlayer adhesive preferably contains a polyolefin resin, a fluorine-based resin, and / or a polyphenylene ether resin. When the circuit board interlayer adhesive contains a polyolefin resin, a fluorine-based resin, and / or a polyphenylene ether resin, an adhesive layer having a lower dielectric constant, high flexibility, and easy to soften quickly when heated can be obtained.
[0057] When the circuit board interlayer adhesive contains other resins, the content of the other resins is, for example, 10 mass% or more, preferably 20 mass% or more, and for example, 95 mass% or less, preferably 90 mass% or less, based on the total amount of the circuit board interlayer adhesive. Also, the content of the polyolefin resin is, for example, 5 mass% or more, preferably 10 mass% or more, and for example, 90 mass% or less, preferably 80 mass% or less, based on the total amount of the circuit board interlayer adhesive.
[0058] Furthermore, the circuit board interlayer adhesive may contain known additives.
[0059] Examples of additives include plasticizers, defoamers, leveling agents, mildew inhibitors, rust inhibitors, matting agents, flame retardants, thixotropic agents, tackifiers, thickeners, lubricants, antistatic agents, surfactants, reaction retarders, antioxidants, UV absorbers, hydrolysis inhibitors, weather stabilizers, heat stabilizers, dyes, inorganic pigments, organic pigments, curing agents, crosslinking agents, silane coupling agents, tack inhibitors, inorganic particles, and organic particles. These can be used alone or in combination of two or more. The ratio and timing of addition of the additives are appropriately set according to the purpose and application.
[0060] The circuit board interlayer adhesive can also be prepared as a solution. More specifically, the polyolefin resin and other resins that are mixed as necessary can be dissolved or dispersed in an organic solvent. The organic solvent is not particularly limited, and may be any known organic solvent.
[0061] In such a case, the solid content concentration of the circuit board interlayer adhesive is, for example, 5 mass % or more, preferably 10 mass % or more, and, for example, 50 mass % or less, preferably 30 mass % or less.
[0062] Furthermore, such an adhesive between circuit board layers contains a polyolefin resin, and therefore has a relatively low dielectric constant and is excellent in adhesion and conformability to irregularities.
[0063] Therefore, the circuit board interlayer adhesive is suitable for use in the production of laminates.
[0064] The laminate is a circuit board or a circuit board material. The circuit board is, for example, a laminate having a conductor layer with a circuit pattern. The circuit board material is, for example, a laminate having a conductor layer without a circuit pattern, which can be processed to form a circuit pattern.
[0065] The laminate is produced by using a circuit board interlayer adhesive. A method for producing a circuit board as a laminate using a circuit board interlayer adhesive will be described in detail below.
[0066] 1 to 4 are cross-sectional views showing steps for manufacturing a circuit board as a first embodiment of a laminate.
[0067] In the following description, the upper side of the paper is referred to as one side, and the lower side of the paper is referred to as the other side.
[0068] 1 to 4, the circuit board 1 is a multilayer circuit board having at least two conductor layers. More specifically, as shown in FIG. 4O, the circuit board 1 includes a first conductor layer 6, a second conductor layer 16 disposed opposite the first conductor layer 6, and an adhesive layer 11 disposed between the first conductor layer 6 and the second conductor layer 16 and bonding the first conductor layer 6 and the second conductor layer 16 together.
[0069] In addition, in the circuit board 1, the adhesive layer 11 is formed from the above-mentioned circuit board interlayer adhesive.
[0070] To manufacture such a circuit board 1, first, a carrier-attached copper foil 2 is prepared as shown in Fig. 1A. The carrier-attached copper foil 2 includes a carrier layer 3 and a copper foil 4 laminated on one side of the carrier layer 3.
[0071] The carrier layer 3 is not particularly limited, and may be a known release sheet. The copper foil 4 is laminated on the carrier layer 3 by a known method. The thickness of the copper foil 4 is appropriately set depending on the purpose and application. The copper foil 4 is also surface-treated as necessary. Examples of the surface treatment include roughening treatment.
[0072] Next, in this method, as shown in FIG. 1B, a first resist layer 5 having a predetermined shape is formed on one surface of the copper foil 4. The first resist layer 5 is formed, for example, by applying a known resist liquid, exposing it to light, and developing it. The first resist layer 5 can also be formed by exposing and etching a dry film resist.
[0073] Next, in this method, as shown in FIG. 1C, a first conductor layer 6 is formed. The first conductor layer 6 is formed, for example, by an electrolytic plating method. In the electrolytic plating method, for example, the carrier layer 3, the copper foil 4, and the first resist layer 5 are immersed in an electrolytic plating solution, and then the copper foil 4 is powered. As a result, the first conductor layer 6 is formed on one surface of the copper foil 4 in a reverse pattern to the first resist layer 5. That is, the first conductor layer 6 has a circuit pattern.
[0074] Next, in this method, as shown in Fig. 2D, the first resist layer 5 is removed by a known method. Next, in this method, as shown in Fig. 2E, the copper foil 4 exposed from the first conductor layer 6 is removed by a known method.
[0075] Next, in this method, an adhesive layer 11 made of a wiring circuit interlayer adhesive is laminated onto the carrier layer 3, the first conductor layer 6 and the copper foil 4, as shown in FIG. 2F.
[0076] More specifically, in this method, for example, a cast film of a wiring circuit interlayer adhesive is prepared. Then, the cast film is pressure-bonded to the carrier layer 3, the first conductor layer 6, and the copper foil 4. As a result, the cast film covers the first conductor layer 6 and the copper foil 4. The cast film also forms an adhesive layer 11.
[0077] On the other hand, in this method, a carrier-attached copper foil 12 is separately prepared. The carrier-attached copper foil 12 includes a carrier layer 13 and a copper foil 14 laminated on the other side of the carrier layer 13. Then, in this method, the copper foil 14 of the carrier-attached copper foil 12 is laminated on an adhesive layer 11, as shown in Fig. 2G.
[0078] Next, in this method, the carrier layer 13 of the carrier-attached copper foil 12 is peeled off, as shown in Fig. 3H. Next, in this method, the copper foil 14 and the adhesive layer 11 are opened by a known method to form a via hole 18, as shown in Fig. 3I. Also, the first conductor layer 6 is exposed from the via hole 18. Next, in this method, the via hole 18 is filled with a conductive material to form a via fill 19, as shown in Fig. 3J. Incidentally, an example of the conductive material is copper.
[0079] Next, in this method, as shown in Fig. 3K, a second resist layer 15 having a predetermined shape is formed on one surface of the copper foil 14. The second resist layer 15 is formed, for example, by applying a known resist liquid, exposing it to light, and developing it. Similarly to the first resist layer 5, the second resist layer 15 can also be formed from a dry film resist.
[0080] Next, in this method, as shown in Fig. 4L, the second conductor layer 16 is formed. The second conductor layer 16 is formed, for example, by electrolytic plating. As a result, the second conductor layer 16 is formed on one surface of the copper foil 14 in a reverse pattern to the second resist layer 15. That is, the second conductor layer 16 has a circuit pattern.
[0081] Next, in this method, as shown in Fig. 4M, the second resist layer 15 is removed by a known method. Next, in this method, as shown in Fig. 4N, the copper foil 14 exposed from the second conductor layer 16 is removed by a known method.
[0082] The method then includes peeling off the carrier layer 3, thereby exposing the copper foil 4, as shown in Figure 4O. As a result, the circuit board 1 is formed.
[0083] In the circuit board 1, the first conductor layer 6 and the second conductor layer 16 are bonded together by the adhesive layer 11.
[0084] That is, the circuit board 1 has an adhesive layer 11 made of the above-mentioned circuit board interlayer adhesive. Therefore, in the circuit board 1, the adhesive layer 11 has a relatively low dielectric constant and is excellent in adhesion and conformability to irregularities.
[0085] It should be noted that the method for producing the circuit board is not limited to the above description, and that the circuit board can be produced using the circuit board interlayer adhesive by other known methods.
[0086] In the above description, a circuit board is exemplified as the laminate, but the laminate may also be a circuit board material that can be processed into a circuit board. An example of the circuit board material is a copper-clad laminate.
[0087] The cross section is a schematic cross section showing a copper-clad laminate as a second embodiment of the laminate.
[0088] 5, copper-clad laminate 21 includes insulating layer 22, conductor layer 24 disposed opposite insulating layer 22, and adhesive layer 23 disposed between insulating layer 22 and conductor layer 24 to bond insulating layer 22 and conductor layer 24. In copper-clad laminate 21, adhesive layer 23 is formed from the above-mentioned circuit board interlayer adhesive.
[0089] The insulating layer 22 is an insulating layer containing a known dielectric. Examples of the dielectric include polyimide resin, epoxy resin, fluororesin, and liquid crystal polymer. These can be used alone or in combination of two or more kinds. The thickness of the insulating layer 22 is appropriately set according to the purpose and application.
[0090] The conductor layer 24 is a thin film made of a conductive material. An example of the conductive material is copper. The conductor layer 24 is formed by a known film formation method. The thickness of the conductor layer 24 is adjusted to be, for example, relatively thin. This allows the circuit pattern to be formed by a subtractive method. The thickness of the conductor layer 24 is, for example, 50 μm or less.
[0091] The adhesive layer 23 is interposed between the insulating layer 22 and the conductor layer 24. The adhesive layer 23 is a dried product of the above-mentioned circuit board interlayer adhesive.
[0092] When manufacturing the copper-clad laminate 21, for example, first, the insulating layer 22 and the conductor layer 24 are prepared. Next, a circuit board interlayer adhesive is applied to one side of the insulating layer 22. Thereafter, the conductor layer 24 is bonded to one side of the circuit board interlayer adhesive, and the circuit board interlayer adhesive is dried. In this way, the copper-clad laminate 21 is obtained. Note that the copper-clad laminate 21 can also be manufactured in the above order. That is, in this method, the circuit board interlayer adhesive is applied to one side of the conductor layer 24. Thereafter, the insulating layer 22 is bonded to one side of the circuit board interlayer adhesive, and the circuit board interlayer adhesive is dried. In this way, the copper-clad laminate 21 is obtained.
[0093] In the copper-clad laminate 21, the insulating layer 22 and the conductor layer 24 are bonded together by the adhesive layer .
[0094] That is, the copper-clad laminate 21 has an adhesive layer 23 made of the above-mentioned circuit board interlayer adhesive. Therefore, in the copper-clad laminate 21, the adhesive layer 23 has a relatively low dielectric constant and is excellent in adhesion and conformability to irregularities.
[0095] In the above description, the adhesive layer 23 and the conductor layer 24 are formed only on one side of the insulating layer 22, but the adhesive layer 23 and the conductor layer 24 may be formed on both sides of the insulating layer 22.
[0096] Furthermore, the copper-clad laminate 21 may not have the insulating layer 22. That is, the conductor layers 24 may be formed on both sides of the adhesive layer 23. In other words, the two conductor layers 24 may be bonded together by the adhesive layer 23. In such a case, the adhesive layer 23 also serves as the insulating layer 22.
[0097] Moreover, the copper-clad laminate 21 can be processed to form a circuit board. More specifically, the conductor layer 24 of the copper-clad laminate 21 can be etched by a known method to form a circuit. As a result, a circuit board is formed as the third embodiment of the laminate, as shown in FIG. 6.
[0098] In such a circuit board, an insulating layer 22 and a circuit made up of a conductor layer 24 are bonded together by an adhesive layer 23 .
[0099] That is, such a circuit board also has the adhesive layer 23 made of the above-mentioned circuit board interlayer adhesive. Therefore, the adhesive layer 23 has a relatively low dielectric constant and is excellent in adhesion and conformability to irregularities. EXAMPLES
[0100] Next, the present invention will be described based on examples and comparative examples, but the present invention is not limited to the following examples. Note that "parts" and "%" are based on mass unless otherwise specified. In addition, the specific numerical values of the blending ratio (content ratio), physical property values, parameters, etc. used in the following description can be replaced with the upper limit value (numerical value defined as "less than or equal to" or "less than") or lower limit value (numerical value defined as "more than or equal to" or "exceeding") of the corresponding blending ratio (content ratio), physical property values, parameters, etc. described in the above "Form for carrying out the invention".
[0101] <Resin> Production Example 1 (Unmodified Propylene-Butene Copolymer (PBR): Resin (A-1)) 900 mL of hexane and 90 g of 1-butene were charged into a 2-liter autoclave that had been thoroughly purged with nitrogen. Then, 1 mmol of triisobutylaluminum was added to the autoclave, and the temperature was raised to 70°C. Next, propylene was supplied to the autoclave, and the total pressure was adjusted to 7 kg / cm. 2 The autoclave was adjusted to 0.30 mmol. The amount of rac-dimethylsilylene-bis{1-(2-methyl-4-phenylindenyl)}zirconium dichloride was then added to the autoclave. The amount of methylaluminoxane was adjusted to 0.30 mmol. The amount of rac-dimethylsilylene-bis{1-(2-methyl-4-phenylindenyl)}zirconium dichloride was adjusted to 0.001 mmol in terms of Zr.
[0102] Then, propylene was continuously fed into the autoclave to maintain the total pressure at 7 kg / cm 2 The temperature was kept at 50°C and 1-butene and propylene were polymerized for 30 minutes. After polymerization, the mixture was degassed and the reaction product was recovered in a large amount of methanol. The reaction product was then dried under reduced pressure at 110°C for 12 hours. This resulted in the production of an unmodified propylene-1-butene copolymer (Resin (A-1)).
[0103] The melting point of resin (A-1) was 78.3° C., the heat of fusion was 29.2 J / g, the weight average molecular weight (Mw) was 330,000, and the propylene content was 67.2 mol %.
[0104] Production Example 2 (Unmodified propylene-butene copolymer: resin (A-2)) 900 mL of hexane and 80 g of 1-butene were charged into a 2-liter autoclave that had been thoroughly purged with nitrogen. Then, 1 mmol of triisobutylaluminum was added to the autoclave, and the temperature was raised to 70° C. Then, propylene was supplied to the autoclave, and the total pressure was adjusted to 7 kg / cm. 2The autoclave was adjusted to 0.30 mmol. The amount of rac-dimethylsilylene-bis{1-(2-methyl-4-phenylindenyl)}zirconium dichloride was then added to the autoclave. The amount of methylaluminoxane was adjusted to 0.30 mmol. The amount of rac-dimethylsilylene-bis{1-(2-methyl-4-phenylindenyl)}zirconium dichloride was adjusted to 0.001 mmol in terms of Zr.
[0105] Then, propylene was continuously fed into the autoclave to maintain the total pressure at 7 kg / cm 2 The temperature was kept at 50°C and 1-butene and propylene were polymerized for 30 minutes. After polymerization, the mixture was degassed and the reaction product was recovered in a large amount of methanol. The reaction product was then dried under reduced pressure at 110°C for 12 hours. This resulted in the production of an unmodified propylene-1-butene copolymer (resin (A-2)).
[0106] The melting point of resin (A-2) was 89.2° C., the heat of fusion was 31.5 J / g, the Mw was 330,000, and the propylene content was 73.5 mol %.
[0107] Production Example 3 (Unmodified propylene-4-methyl-1-pentene copolymer: resin (A-3)) 300 mL of hexane and 450 mL of 4-methyl-1-pentene were charged into a 1.5-liter autoclave that had been thoroughly purged with nitrogen. Then, 0.75 mmol of triisobutylaluminum was added to the autoclave, and the temperature was raised to 60°C. Then, propylene was supplied to the autoclave, and the total pressure was adjusted to 0.40 MPa (gauge pressure). Then, methylaluminoxane and diphenylmethylene(1-ethyl-3-t-butyl-cyclopentadienyl)(2,7-di-t-butyl-fluorenyl)zirconium dichloride were added to the autoclave. The amount of methylaluminoxane was 1 mmol in terms of Al. Also, the amount of diphenylmethylene(1-ethyl-3-t-butyl-cyclopentadienyl)(2,7-di-t-butyl-fluorenyl)zirconium dichloride was 0.01 mmol.
[0108] Propylene was then continuously fed into the autoclave, and 4-methyl-1-pentene and propylene were polymerized for 60 minutes. After polymerization, the reaction was stopped, and the autoclave was depressurized to atmospheric pressure. The reaction product was then recovered with acetone. The reaction product was then dried under reduced pressure at 100°C for 12 hours. This resulted in the production of an unmodified propylene-4-methyl-1-pentene copolymer (resin (A-3)).
[0109] The melting point of resin (A-3) was not observed, and resin (A-3) had Mw of 320,000 and a propylene content of 28 mol %.
[0110] Production Example 4 (Maleic Acid Modified Propylene-Butene Copolymer: Resin (A-4)) 3 kg of resin (A-2) was added to 10 L of toluene and heated to 145°C under a nitrogen atmosphere. This gave a toluene solution of the resin. Next, 382 g of maleic anhydride and 175 g of di-tert-butyl peroxide were added to the solution over 4 hours, and the mixture was reacted at 145°C for 2 hours. Acetone was then added to the reaction solution to precipitate the reaction product. The precipitate was then filtered, washed, and vacuum dried. This gave a maleic acid-modified propylene-1-butene copolymer (resin (A-4)).
[0111] The melting point of resin (A-4) was 85.9° C., the heat of fusion was 29.9 J / g, the Mw was 110,000, and the proportion of maleic anhydride was 1 part by mass per 100 parts by mass of the total amount of resin (A-4).
[0112] Production Example 5 (Mixture of Maleic Acid Modified Propylene-1-Butene Copolymer and Maleic Acid Modified SEPS: Resin (A-5)) 1.5 kg of resin (A-1) and 1.5 kg of Septon 2002 (product name, styrene-ethylene-propylene-styrene copolymer (SEPS), manufactured by Kuraray) were added to 10 L of toluene and heated to 145°C under a nitrogen atmosphere. This resulted in a toluene solution of the resin. Next, 382 g of maleic anhydride and 175 g of di-tert-butyl peroxide were added to the solution over 4 hours and reacted at 145°C for 2 hours. After that, acetone was added to the reaction liquid to precipitate the reaction product. The precipitate was filtered, washed, and vacuum dried. This resulted in a mixture of maleic acid modified propylene-1-butene copolymer and maleic acid modified styrene-ethylene-propylene-styrene copolymer (resin (A-5)).
[0113] The melting point of resin (A-5) was 75.6° C., the heat of fusion was 14.7 J / g, the Mw was 98,000, and the proportion of maleic anhydride was 1 part by mass per 100 parts by mass of the total amount of resin (A-5).
[0114] Production Example 6 (Maleic acid modified styrene-ethylene-butylene-styrene copolymer: resin (A-6)) 3 kg of Kraton G1652M (product name, styrene-ethylene-butylene-styrene copolymer (SEBS), manufactured by Kuraray) was added to 10 L of toluene and heated to 145°C under a nitrogen atmosphere. This resulted in a toluene solution of resin. Next, 382 g of maleic anhydride and 175 g of di-tert-butyl peroxide were added to the solution over 4 hours, and the reaction was carried out at 145°C for 2 hours. After that, acetone was added to the reaction liquid to precipitate the reaction product. The precipitate was filtered, washed, and vacuum dried. This resulted in a maleic acid-modified styrene-ethylene-butylene-styrene copolymer (resin (A-6)).
[0115] The melting point of resin (A-6) was not observed. The heat of fusion of resin (A-6) was also not observed. Mw of resin (A-6) was 100,000, and the proportion of maleic anhydride was 2 parts by mass relative to 100 parts by mass of the total amount of resin (A-6).
[0116] Production Example 7 (Maleic Acid Modified Propylene-4-Methyl-1-Pentene Copolymer: Resin (A-7)) 3 kg of resin (A-3) was added to 10 L of toluene and heated to 145°C under a nitrogen atmosphere. This resulted in a toluene solution of the resin. Next, 382 g of maleic anhydride and 175 g of di-tert-butyl peroxide were added to the solution over 4 hours, and the mixture was reacted at 145°C for 2 hours. Acetone was then added to the reaction solution to precipitate the reaction product. The precipitate was then filtered, washed, and vacuum dried. This resulted in a maleic acid-modified propylene-4-methyl-1-pentene copolymer (resin (A-7)).
[0117] The melting point of the resin (A-7) was not observed. The Mw of the resin (A-7) was 100,000, and the proportion of maleic anhydride was 1 part by mass per 100 parts by mass of the total amount of the resin (A-7).
[0118] Production Example 8 (Ethylene-propylene copolymer (Resin A-8)) 1 L of dehydrated and purified hexane was added to a continuous polymerization reactor equipped with an agitator and thoroughly purged with nitrogen.
[0119] Then, a 96 mmol / L hexane solution of ethylaluminum sesquichloride was continuously fed into the reactor at a flow rate of 500 mL / h for 1 hour.
[0120] Next, 500 mL / h of a hexane solution of 16 mmol / L VO(OC2H5)Cl2 as a catalyst and 500 mL / h of hexane were continuously fed to the reactor.
[0121] Next, 47 L / h of ethylene gas, 47 L / h of propylene gas, and 20 L / h of hydrogen gas were supplied to the reactor using a bubbling tube. A coolant was circulated in the jacket outside the reactor. Meanwhile, the reaction liquid was extracted from the top of the reactor and adjusted so that the reaction liquid was always 1 L.
[0122] The reaction solution was deashed with hydrochloric acid and poured into a large amount of methanol, and the precipitated reaction product was then dried under reduced pressure at 130°C for 24 hours.
[0123] This resulted in the production of ethylene-propylene copolymer (EPR) (resin A-8).
[0124] The ethylene content of resin (A-8) was 55.9 mol % and Mw was 14,000.
[0125] <Interlayer adhesive for circuit boards> reference Example 1 100 g of resin (A-5) was dissolved in 400 g of toluene under heating to prepare circuit board interlayer adhesive A.
[0126] reference Example 2 A circuit board interlayer adhesive B was prepared by dissolving 80 g of resin (A-4) and 20 g of resin (A-8) in 400 g of toluene with heating.
[0127] reference Example 3 A circuit board interlayer adhesive C was prepared by dissolving 100 g of resin (A-4) in 400 g of toluene under heating.
[0128] reference Example 4 50 g of resin (A-7) was dissolved in 450 g of toluene by heating to prepare a circuit board interlayer adhesive D.
[0129] reference Example 5 4 parts by mass of methylcyclohexane was mixed with 15 parts by mass of n-propyl acetate to prepare a mixed solvent of methylcyclohexane and n-propyl acetate.
[0130] Next, 63 g of Kraton G1652M (product name, styrene-ethylene-butylene-styrene copolymer (SEBS), manufactured by Kuraray) was dissolved in 152 g of the mixed solution by heating.
[0131] Meanwhile, 46.3 g of methyl methacrylate, 2.5 g of n-butyl acrylate, 11.7 g of n-butyl methacrylate, 2.5 g of methacrylic acid, 0.76 g of Perbutyl O (manufactured by NOF Corp.), and 107 g of n-propyl acetate were mixed uniformly to prepare a monomer solution.
[0132] Next, the monomer solution was added dropwise to the Kraton G1652M solution over 2 hours and polymerized at 95° C. After that, 114 g of n-propyl acetate was added to the reaction solution, thereby preparing a circuit board interlayer adhesive E.
[0133] reference Example 6 100 g of resin (A-6) was dissolved in 400 g of toluene under heating to prepare circuit board interlayer adhesive F.
[0134] reference Example 7 A fluorine-based resin solution (product name Fluon+EA-2000, manufactured by AGC) was prepared.
[0135] Next, 30 g of resin (A-8) was added to 70 g of the fluororesin (solid content).
[0136] Then, toluene was added to adjust the total amount to 500 g, thereby preparing circuit board interlayer adhesive G.
[0137] reference Example 8 A fluororesin solution was prepared. Next, 30 g of polyisobutylene (product name: Himol 4H, manufactured by Petrochemical Co., Ltd.) was added to 70 g of the fluororesin (solid content).
[0138] Then, toluene was added to adjust the total amount to 500 g. Thus, circuit board interlayer adhesive H was prepared.
[0139] Example 9 A fluororesin solution was prepared. Next, the circuit board interlayer adhesive A was added to 50 g of the fluororesin (solid content) so that the resin component of the circuit board interlayer adhesive A was 50 g.
[0140] Then, toluene was added to adjust the total amount to 500 g. Thus, a circuit board interlayer adhesive I was prepared.
[0141] Example 10 A fluororesin solution was prepared. Next, the circuit board interlayer adhesive B was added to 50 g of the fluororesin (solid content) so that the resin component of the circuit board interlayer adhesive B was 50 g.
[0142] Then, toluene was added to adjust the total amount to 500 g, thereby preparing circuit board interlayer adhesive J.
[0143] Example 11 A fluororesin solution was prepared. Next, the circuit board interlayer adhesive C was added to 50 g of the fluororesin (solid content) so that the resin component of the circuit board interlayer adhesive C was 50 g.
[0144] Then, toluene was added to adjust the total amount to 500 g, thereby preparing circuit board interlayer adhesive K.
[0145] Example 12 A fluororesin solution was prepared. Next, the circuit board interlayer adhesive D was added to 50 g of the fluororesin (solid content) so that the resin component of the circuit board interlayer adhesive D was 50 g.
[0146] Then, toluene was added to adjust the total amount to 500 g, thereby preparing circuit board interlayer adhesive L.
[0147] Comparative Example 1 A fluororesin solution was prepared. Toluene was then added to adjust the total amount to 500 g. Thus, a circuit board interlayer adhesive M was prepared.
[0148] <Evaluation> (1) Dielectric constant and dielectric tangent A predetermined amount of the circuit board interlayer adhesive was applied onto a 100 μm-thick release PET sheet and dried at 100° C. for 3 minutes. This resulted in a coating film with a dry thickness of approximately 60 μm. The coating film was then molded into a rectangular shape.
[0149] Then, the relative dielectric constant and dielectric loss tangent of the coating film were measured at a frequency of about 10 GHz using a cavity resonator method. Note that a vector network analyzer HP8510B (manufactured by Keysight Technologies) was used as the measuring device. The measuring method was in accordance with JIS R 1641 (2007).
[0150] (2) Adhesion A predetermined amount of the circuit board interlayer adhesive was applied to an aluminum foil and dried at 100°C for 1 minute. This resulted in a coating film with a dry thickness of about 3 μm. The coating film was then thermocompressed onto a copper plate. The thermocompression conditions were 180°C, 0.3 MPa, and 1 second.
[0151] The coating was then cooled and a 15 mm wide cut was made in the aluminum foil.
[0152] Thereafter, the peel strength between the aluminum foil and the copper plate was measured using a universal tensile tester at a crosshead speed of 50 mm / min and a peel angle of 180°.
[0153] (3) Ability to follow uneven surfaces A predetermined amount of the circuit board interlayer adhesive was applied to an aluminum foil and dried for 2 minutes at 100° C. This resulted in a coating film with a dry thickness of about 30 μm.
[0154] On the other hand, a circuit board with an exposed conductor layer (see FIG. 2E) was prepared. Then, the coating film was thermocompression bonded to the conductor layer. The thermocompression bonding conditions were 180° C., 0.3 MPa, and 3 seconds. Then, the cross section of the bonded portion was observed with a digital microscope. Then, the unevenness-following ability was evaluated according to the following criteria.
[0155] ◯: No gap was observed between the coating film and the circuit.
[0156] ×: Gaps were observed between the coating film and the circuit.
[0157] [Table 1]
[0158] Details of the abbreviations in the table are given below.
[0159] Maleated PBR: Maleic acid modified propylene-butene copolymer Maleated C3-4MP: Maleic acid modified propylene-4-methyl-1-pentene copolymer Maleated SEPS: Maleic acid modified styrene-ethylene-propylene-styrene copolymer Maleated SEBS: Maleic acid modified styrene-ethylene-butylene-styrene copolymer EPR: Ethylene-propylene copolymer SEBS: Styrene-ethylene-butylene-styrene copolymer Acrylic resin: Methyl methacrylate / n-butyl acrylate / n-butyl methacrylate / methacrylic acid copolymer Fluorine resin: Product name Fluon+EA-2000, manufactured by AGC [Explanation of symbols]
[0160] 1 Multilayer circuit board 2 Copper foil with carrier 3. Carrier Layer 4 Copper foil 5 Resist layer 6 First conductor layer
Claims
1. Contains a polyolefin resin and a fluorine-based resin, The circuit board interlayer adhesive, wherein the polyolefin resin contains an acid-modified polyolefin resin.
2. With respect to the total amount of circuit board interlayer adhesive, The proportion of the polyolefin resin is 5% by mass or more and 90% by mass or less, 2. The circuit board interlayer adhesive according to claim 1, wherein the proportion of the fluorine-based resin is 10% by mass or more and 95% by mass or less.
3. A first conductor layer; A second conductor layer disposed opposite the first conductor layer; an adhesive layer disposed between the first conductor layer and the second conductor layer and adhering the first conductor layer and the second conductor layer; Equipped with A laminate, wherein the adhesive layer comprises the circuit board interlayer adhesive according to claim 1 or 2.
4. An insulating layer; a conductor layer disposed opposite the insulating layer; an adhesive layer disposed between the insulating layer and the conductor layer and adhering the insulating layer and the conductor layer; Equipped with A laminate, wherein the adhesive layer comprises the circuit board interlayer adhesive according to claim 1 or 2.
Citation Information
Patent Citations
Printed wiring board, polyolefinic resin composition, and method for manufacturing of printed wiring board
JP2001094262A
Transparent conductive sheet and touch panel
JP2014096241A
Copper foil for high-frequency circuit, copper clad laminate sheet for high-frequency circuit, printed wiring board for high-frequency circuit, copper foil with carrier for high-frequency circuit, electronic apparatus, and method of manufacturing printed wiring board
JP2014225650A
Resin composition for printed circuit boards and production method
JP2019065061A
Hot melt adhesive resin laminate and laminate
JP2019137853A